2008
DOI: 10.1097/01.hmr.0000324909.49766.de
|View full text |Cite
|
Sign up to set email alerts
|

What can family medicine practices do to facilitate knowledge management?

Abstract: Steps to facilitate KM should be considered when evaluating more intensive and costly organizational solutions for enhancing family medicine practice performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Evidently, developing knowledge relies on social tools. Articulating tacit knowledge to explicit manifests through collective reflection (Orzano et al ., ), ‘huddles’ or brief team meetings (Orzano et al ., ) and dialogical exchange (Quinlan, ). Still, eHealth technologies, like decision support systems, active directories and portals, facilitate dynamic interaction among clinical practitioners.…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, developing knowledge relies on social tools. Articulating tacit knowledge to explicit manifests through collective reflection (Orzano et al ., ), ‘huddles’ or brief team meetings (Orzano et al ., ) and dialogical exchange (Quinlan, ). Still, eHealth technologies, like decision support systems, active directories and portals, facilitate dynamic interaction among clinical practitioners.…”
Section: Resultsmentioning
confidence: 99%
“…Physicians in primary care fields and data-intensive specialties such as oncology bear a particularly heavy burden in consuming and managing the amount of information available to them [1-3]. Over the next decade, the cognitive limitation of the traditional model, wherein physicians are expected to learn, retain, and call upon an ever-expanding body of medical knowledge, will become more challenging to navigate.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary analyses suggested that improved practice KM processes are associated with improved diabetes mellitus outcomes (Orzano, Ohman-Strickland, et al, 2007) and that specific organizational enablers, such as effective leadership and communication, can enhance KM processes (Orzano, Ohman-Strickland, & Patel, 2008c). In this article, we refined our initial model built on secondary data; with primary data, we verified our understanding and contrasted how primary care practices exhibit KM and explained why KM deserves attention in medical home redesign initiatives (Doran et al, 2006;Martin et al, 2004).…”
mentioning
confidence: 81%
“…This study builds on a focused inquiry involving a series of studies leading to our characterization of KM and its connection with performance (Orzano et al, 2006(Orzano et al, , 2008a(Orzano et al, , 2008b(Orzano et al, , 2008cOrzano, Ohman-Strickland, et al, 2007;Orzano, Scott, et al, 2007;. Certainly, the current report is limited to an analysis of four practices (with in-depth reporting on one high-performing and one low-performing practice), reflects viewpoints of the research team, and lacks proof of causation.…”
Section: Limitations Of the Study And Suggestions For Further Researchmentioning
confidence: 99%